Helping the invisible hand: A theory of endogenous mutual concern - Martin Kolmar (Brown University, Department of Economics, 2001)
This paper develops a theory of endogenous mutual concern. The mutual concern or the morality of economic agents is seen as a means to reduce the inefficiencies of markets in an environment where the enforcement of property rights is castly. We show that rational agents have an incentive to invest resources to create a mutual concern. Furthermore, the strength of the mutual concern depends on the technologies of production and appropriation and defense. People in economies with a high natural produetivity invest more resourees in the creation of a mutual concern than people in economies with low natural productivity. By the same token, morality is a means to reduce the frictions in an economy only if the decisiveness of appropriation and defense is relatively similar. – Productivity ; Anarchy ; Morality
Keywords: D74; K42; Z13; 330; Ethik; Marktmechanismus; Nash-Gleichgewicht; Theorie; Soziale Norm